Effect of Supplemental Language Therapy on Cortical Neuroplasticity and Language Outcomes in Children with Hearing Loss - Anu Sharma; Kayla Cormier; Jim Grigsby (Brain Sciences, 2025)
Background/Objectives: The cortical auditory evoked potential P1 response is a biomarker of cortical auditory maturation for tracking longitudinal cortical maturation in children with hearing loss after treatment with hearing aids and/or cochlear implants. In conjunction with hearing treatments, children with hearing loss commonly receive language therapy services. However, the effect of language therapy on cortical maturation in hearing loss is less well studied. Methods: This study explored auditory cortical maturation changes, using the P1 response, with coinciding language changes, utilizing the Preschool Language Scales test, following approximately six months of supplemental listening and spoken language therapy services in 39 children with hearing aids or cochlear implants. Results: Following supplemental language therapy, P1 latencies significantly decreased in all children, at a rate found to be significantly faster than expected for typical maturation. Language scores also significantly improved beyond expected maturation effects and were correlated with P1 latencies following supplemental therapy. Overall, with approximately six months of therapy, the children in this study made significantly greater gains of 9 to 10 months in total language and expressive communication. A subgroup analysis revealed that children with cochlear implants showed significantly lower language scores than their chronological age following supplemental therapy, while children with hearing aids obtained language scores that were not significantly different to their chronological age at follow-up. Conclusions: Overall, the results from this study showed that supplemental language therapy resulted in more typical auditory cortical maturation and improved language abilities and that the P1 CAEP response can objectively track neuroplastic changes in children as a function of language therapy provided in conjunction with hearing aids and CIs.